Outbreak investigation of Chikungunya fever in Kapanewon Banguntapan, Bantul, Yogyakarta: a lesson learned - Gusrina, Sylvia; Lestari, Nining Puji; Aryanto, Samsu; Wiratama, Bayu Satria (Universitas Gadjah Mada, 2024)
Purpose: The investigation was conducted to confirm the Chikungunya outbreak in Banguntapan. Bantul. from November 2021 to January 2022 and identify the risk factors for control measures. Methods: We conducted a 1:1 case-control study. Cases were residents of the six hamlets in Banguntapan with sudden fever and arthralgia from December 2021 to February 14. 2022. Controls were residents of the same neighborhood with no symptoms. We collected demographics, risk factors, and environmental data using standardized questionnaires through direct interviews and observation. For diagnosis confirmation, we examine the case blood serum for laboratory testing. Logistic regression was used to analyze the risk factors. Results: We identified 151 Chikungunya suspects (Attack-rate/AR 13.6%) of 1111 total population. The highest AR by gender and location were in women (16.3%) and Genengan hamlet in Jambidan village (45.6%), respectively. Fever (92.1%) and muscle pain (81.7%) are the significant symptoms. The latest larval rate average was 13% lower than the national target. More than one-third of the cases were in the acute phase of infection. Multivariate analysis showed close contact of cases (aOR 22.79; 95% CI: 7.01–74.17) and community habit of hanging clothes in the house (aOR 2.42; 95% CI: 1.01–5.82) significantly associated with the Chikungunya outbreak. Conclusion: There was a Chikungunya outbreak in Jambidan and Tamanan Village, Banguntapan, from November 8, 2021, to January 31, 2022. Therefore, we recommend that the DHO strengthen health education related to protective action while having close contact with suspects and the habit of hanging wardrobes in the house as risk factors associated with the outbreak.